Diet Kalsium pada Ibu Hamil - Kartika Adyani (EMBRIO: Jurnal Kebidanan, 2020)
Calcium is a mineral that is essential for bone formation, muscle contraction, and enzymes and hormone metabolism. Tissue formation in the fetus requires calcium so that the need for calcium in pregnant women increases. Pregnant women who get calcium intake <500 mg / day are at risk of reducing bone mass during pregnancy. the lowest calcium intake in the world occurs in developing countries, especially Asia. Calcium supplementation in pregnancy is associated with a reduced risk of hypertension in pregnancy, preterm birth, and an increase in birth weight. The purpose of this article is to find out the calcium diet for pregnant women. This scientific article is a literature review. The results of this literature study describe the benefits of calcium for pregnant women, the factors that influence calcium intake in pregnant women, the impact of calcium deficiency for pregnant women. The conclusion of this article is that calcium is needed by pregnant women for the growth and development of the fetus in the womb. Appropriate calcium intake (± 1300 mg/day) can significantly reduce the risk of preterm birth.